Determination of the threshold value of chloride concentration of seawater utilized in the production of reinforced concrete (RC) specimens using gravimetric analysis - Canapi, Jezreel D.
Presence of chlorides in marine environments to which reinforced concrete is exposed to, promotes corrosion of the embedded steel, by diffusion through the concrete cover over time until it reaches the reinforcing bars. The objective of this study was to determine the threshold value of the chloride concentration that would result to the maximum rate of corrosion of the embedded steel in the reinforced concrete (RC) specimens. Gravimetric analysis is employed in determining the rate of corrosion of the RC specimens. Graphs of relationships between the chloride concentration of the liquid to be used in the RC specimens, number of days prior to testing period and corrosion rate of the rebars in the RC specimens are constructed. Results showed that the approximate threshold value of the chloride concentration that maximizes the rate of corrosion of the embedded steel in the RC specimens for the 1st batch and the 2nd batch are 4.72% and 3.74%, respectively. Similar trends for the plots of the corrosion rate vs. the number of days in which the specimens are placed on the curing tank are observed for both batches of RC specimens. At around 20 days after the RC specimens are placed in the curing tank, a significant increase in corrosion rate in the RC specimens from none can be discerned. After the significant increase in the corrosion rate, an evident "plateauing" of the graph can be seen, and at around 50 to 60 days, there will be a steeper increase in the corrosion rates observed for both batches of RC specimens.